Microbial and metabolic characterization of organic artisanal sauerkraut fermentation and study of gut health-promoting properties of sauerkraut brine - Gaudioso, Giulia; Weil, Tobias; Marzorati, Giulia; Solovyev, Pavel; Bontempo, Luana; Franciosi, Elena; Bertoldi, Luigi; Pedrolli, Carlo; Tuohy, Kieran Michael; Fava, Francesca (Frontiers in Microbiology, 2022)
Sauerkraut is a traditionally fermented cabbage and recent evidence suggests it has beneficial properties for human health. In this work, a multi-disciplinary approach was employed to characterize the fermentation process and gut health promoting properties of locally produced, organic sauerkraut from two distinct producers, SK1 and SK2. 16S rRNA metataxonomics showed that bacterial diversity gradually decreased as fermentation progressed. Differences in sauerkraut microbiota composition were observed between the two producers, especially at the start of fermentation. Lactic acid bacteria (LAB) dominated the microbiota after 35 days, with Lactiplantibacillus being the dominant genus in both sauerkraut products, together with Leuconostoc and Paucilactobacillus in SK1, and with Pediococcus, Levilactibacillus and Leuconostoc in SK2. LAB reached between 7 and 8 Log CFU/mL brine at the end of fermentation (35 days), while pH lowering happened within the first week of fermentation. 220 LAB strains, corresponding to 133 RAPD-PCR biotypes, were successfully isolated. Lactiplantibacillus plantarum and Lactiplantibacillus pentosus accounted for 67% of all SK1 isolates, and Lactiplantibacillus plantarum/paraplantarum and Leuconostoc mesenteroides represented 72% of all the isolates from SK2. 1H-NMR analysis revealed significant changes in microbial metabolite profiles during the fermentation process, with acetic and lactic acids as well as amino acids, amines and uracil being the dominant metabolites quantified. Sauerkraut brine did not affect trans-epithelial electrical resistance through a Caco-2 cell monolayer as a measure of gut barrier function. However, a significant modulation of inflammatory response after LPS stimulation was observed in PBMCs-Caco-2 coculture. Sauerkraut brine supported a robust inflammatory response to endotoxin, by increasing TNF-α and IL-6 production while also stimulating the anti-inflammatory IL-10, therefore suggesting positive resolution of inflammation after 24 hours and supporting the potential of sauerkraut brine to regulate intestinal immune function.